The main subjective manifestations of computer vision syndrome - I. G. Ovechkin; M. E. Konovalov; O. G. Leksunov; E. I. Kovrigina; V. E. Yudin (Российский офтальмологический журнал)
Purpose: to analyze the main subjective manifestations of computer vision syndrome (CVS).Materials and methods. We examined 100 patients aged 24–36, whose daily professional activity (at least for 2 years) involved visual-intensive work associated with electronic display systems (at least 4 hours a day) and requiring a sufficiently high responsibility level. All patients had complaints characteristic of asthenopia in CVS, indicating the stages of subcompensation or decompensation (in accordance with the recommendations of the Expert Council for Accommodation and Refraction of All-Russian Public Organization “Association of Ophthalmologists”). Each patient underwent an individual interview which was conducted according to the standard technique in order to identify the range of complaints that arise from long-term work with a computer.Results. The most common ocular (visual) subjective manifestations included the foreign body sensation, “sand” and itching in the eye; dry eyes; tiredness of vision; redness of the eyeballs; tension of eye muscles; “cramps”, burning in the eye — (which was mentioned by 100% of the testees). Other manifestations were somatic (headache — 89%; pain in the neck and the back — 79%), professional (patients wishing to interrupt work or take a break — 83%; periodic loss of visual concentration — 77%) and medico-psychological (the fear of vision deterioration — 65%).Conclusion. The established subjective manifestations improve the prospects of CVS diagnostics and can serve as basis for assessing the quality of life of patients engaged in vision intensive work.